Organocatalyzed Synthesis and Antibacterial Activity of Novel Quinolino Annulated Analogues of Azepinones. (5th July 2018) - Arora, Deepika; Dwivedi, Jaya; Arora, Sakshi; Kumar, Sudesh; Kishore, Dharma
Abstract : Starting from dimedone, two methodologies for synthesizing novel quinolino annulated azepinones have been reported. The protocol involves azepinone synthesis by the action of a newly synthesized organocatalyst derived from the reaction of TCT and DMF on oxime derivatives (5 and9 ), which were obtained by the reaction of acridine dione derivatives (4 and8 ) with hydroxylamine hydrochloride. The derivatives4 and8 were obtained by the reaction of1 with anthranilic acid2 and isatoic anhydride7, respectively. The synthesis of all the compounds was confirmed initially by TLC followed by spectral analysis through IR, 1 H NMR, 13 C NMR, mass spectrometry, and elemental analysis. The results that emanated on the evaluation of the antibacterial activity of azepinones against two Gram‐positive and two Gram‐negative test organisms using disc diffusion method have also been discussed. Compounds6c, 6d, 6e, 10c, and10e have been found to display better inhibitory activity than standard drugs streptomycin and tetracycline. The minimum inhibitory concentration and IC50 values for the compounds under study as well as of standard drugs were calculated. The maximum inhibition by bacterial strains was observed at 150 μg/mL. Abstract :